Photophysical and Photovoltaic Characterization of Flourene-Anthracene-Benzothiadiazole Based Donor-Acceptor Type Copolymers for Bulk Heterojunction Polymer Solar Cells - Dogan, Seda; Tore, Nesrin; Karsli, Adem; Parlak, Elif Alturk; Turksoy, Figen; Gunes, Serap (AMER SCIENTIFIC PUBLISHERS, 2019)
Photophysical and photovoltaic properties of donor-acceptor type fluorene-anthracene and benzothiadiazole based copolymers were investigated. Bulk heterojunction polymer solar cells were fabricated. The distinction of the two polymers lies in the difference between the donor-acceptor ratios. We have compared their photovoltaic performances and investigated the effect of thickness of blend films on the device performance. The polymer having higher fluorene content exhibited higher photovoltaic performance. We have also observed that one of the polymers depending on the donor-acceptor ratio can act both as a donor and an acceptor in bulk heterojunction polymer solar cells. The solar cells fabricated from thinner blend films showed better photovoltaic performance. It was observed that the thickness slightly affects the morphology of the blend films.
Keywords: Polymer Solar Cells; Donor-Acceptor Ratio; Organic Solar Cells; Fluorene; Benzothiadiazole; Anthracene; INTERNAL QUANTUM EFFICIENCY; MORPHOLOGY; Engineering; Science & Technology - Other Topics; Physics